Propolis-enhanced Calcium Hydroxide Combination for Direct Pulp Capping: Impact on Oxidative Stress Markers in Wistar Rat Teeth - Widjiastuti, Ira; Kunarti , Sri; Ningtyas , Evri Kusumah; Atikah , Ayu Rafania; Basalamah, Khadijah Fauzi; Puspita , Amelia Evita; Widianti , Novelia Ayu; Tengku Ahmad Noor, Tengku Natasha Eleena binti (Iranian Endodontic Journal, 2024)
Introduction: This study explored the effects of propolis extract calcium hydroxide (Ca(OH)2) combination on malondialdehyde and superoxide dismutase expression in dental pulp, aiming to assess its potential as a direct pulp capping material. Materials and Methods: Thirty male Wistar rats were randomly assigned to three groups. Mandibular molar teeth were prepared using a low-speed round bur. In Group I, no material was applied; in Group II, teeth were treated with Ca(OH)2; and in Group III, teeth were treated with Propolis extract-Ca(OH)2, followed by Cention N filling. Immunohistochemistry was conducted on pulp tissue samples obtained on the third and seventh days post-treatment to assess malondialdehyde and superoxide dismutase expression. Statistical analyses included the Shapiro-Wilk test, Levene test, ANOVA, and Tukey’s HSD. Results: The samples treated with propolis extract-Ca(OH)2 combination exhibited significantly lower malondialdehyde expression on both days compared to samples treated with Ca(OH)2 (P<0.05), indicating reduced oxidative stress. Superoxide dismutase expression in the propolis extract-Ca(OH)2 group was higher (P<0.05), suggesting an enhanced antioxidant activity. The control group showed intermediate results. Statistical analyses confirmed significant differences between groups for both malondialdehyde and superoxide dismutase expressions (P<0.05). Conclusion: The study suggests that the propolis extract-Ca(OH)2 combination holds promise for direct pulp capping applications by minimizing oxidative stress and promoting antioxidant defense mechanisms in dental pulp.